2019
DOI: 10.1093/mnras/stz3149
|View full text |Cite
|
Sign up to set email alerts
|

Scale-invariance in the repeating fast radio burst 121102

Abstract: The statistical properties of the repeating fast radio burst FRB 121102 are investigated. We find that the cumulative distributions of fluence, flux density, total energy and waiting time can be well fitted by the bent power law. In addition, the probability density functions of fluctuations of fluence, flux density and total energy well follow the Tsallis q-Gaussian distribution. The q values keep steady around q ∼ 2 for different scale intervals, indicating a scale-invariant structure of the bursts. The stat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 45 publications
(79 reference statements)
3
23
0
Order By: Relevance
“…The consistency of q values for different temporal interval scale indicates the scale invariance of SGRs. This property have been found in the earthquakes (Wang et al 2015) and repeating FRBs (Lin & Sang 2020). Hence they might share the similar emission mechanism.…”
Section: Probability Density Functions Of Fluctuationssupporting
confidence: 61%
See 3 more Smart Citations
“…The consistency of q values for different temporal interval scale indicates the scale invariance of SGRs. This property have been found in the earthquakes (Wang et al 2015) and repeating FRBs (Lin & Sang 2020). Hence they might share the similar emission mechanism.…”
Section: Probability Density Functions Of Fluctuationssupporting
confidence: 61%
“…Hence in this paper we study the statistical properties of the dimensionless fluctuation, defined as zn = Zn/σ. The fluctuations of bursts of SGR J1550-5418 and repeating FRB 121102 have been shown to follow the Tsallis q-Gaussian distribution (Chang et al 2017;Lin & Sang 2020). The Tsallis q-Gaussian function (Tsallis 1988;Tsallis et al 1998) is defined as…”
Section: Probability Density Functions Of Fluctuationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Past studies of the energy distribution (Gourdji et al 2019;Lin & Sang 2020;Cruces et al 2021;Aggarwal et al 2021;Hewitt et al 2021) have found different power-law indices, but low numbers and different energy dependent completeness thresholds have complicated the comparisons. Li et al (2021b) found a bimodal energy distribution and that the higher energy bursts were only detectable in their earlier observations so that not only the rate changes but also the form of the energy distribution.…”
Section: Burst Energy Distributionmentioning
confidence: 99%